2013
DOI: 10.1515/bmt-2012-0073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical practicability of intraoperative optical imaging comparing three different camera setups

Abstract: Intraoperative optical imaging (IOI) is a method to visualize functional activated brain areas during brain surgery using a camera system connected to a standard operating microscope. Three different high-resolution camera systems (Hamamatsu EB-CCD C7190-13W, Hamamatsu C4742-96-12G04, and Zeiss AxioCam MRm) have been evaluated for suitability to detect activated brain areas by detecting stimulation-dependent blood volume changes in the somatosensory cerebral cortex after median nerve stimulation. The image qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In X-ray digital radiography and computed tomography, the low light level imaging capability of an EBCCD allows the reduction of the irradiation dose to the patient [ 18 , 19 ]. EBCCDs have also been evaluated for visualising stimulated functional brain areas during surgery [ 16 ].…”
Section: Some Applications Of Eb-sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In X-ray digital radiography and computed tomography, the low light level imaging capability of an EBCCD allows the reduction of the irradiation dose to the patient [ 18 , 19 ]. EBCCDs have also been evaluated for visualising stimulated functional brain areas during surgery [ 16 ].…”
Section: Some Applications Of Eb-sensorsmentioning
confidence: 99%
“…Single photon detection is also possible with electron-bombarded (EB) sensors, where a photocathode is placed in front of the sensor, and a single photoelectron is accelerated through a high voltage directly into a solid state sensor. EB sensors are conceptually similar to old silicon intensified target television cameras, and have found applications in microscopy [ 12 , 13 ] and biological low-light imaging [ 14 , 15 , 16 ], optical spectroscopy [ 17 ] and radiography [ 18 , 19 ]. The advantages of EB sensors over intensified camera systems include reduced sensor size and weight, increased sensitivity and dynamic range, faster response time, and better contrast and resolution.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a suitable camera setup with an easy and safe handling of the equipment is required for any intraoperative neurosurgical application. Therefore, in the third paper of this journal, Sobottka et al [ 6 ] describe three different high-resolution camera systems connected to the standard operating microscope. The systems are evaluated in 14 brain tumor patients and prove suitability to detect activated brain areas in the somatosensory cerebral cortex after median nerve stimulation.…”
Section: Intraoperative Optical Imaging In Neurosurgerymentioning
confidence: 99%
“…The systems are evaluated in 14 brain tumor patients and prove suitability to detect activated brain areas in the somatosensory cerebral cortex after median nerve stimulation. Several possible causes and influencing factors for no or negative optical imaging results were observed that, however, could be controlled with a suitable image acquisition and data analysis technique in the great majority of cases [ 6 ]. Recently, it could be shown that intraoperative optical imaging is highly reliable for the identification and visualization of functionally intact somatosensory cortex with a sensitivity of 94.4% and a specificity of close to 100% [ 7 ].…”
Section: Intraoperative Optical Imaging In Neurosurgerymentioning
confidence: 99%
See 1 more Smart Citation